Students’ Perception on English Camp Program in MA Female Ar-Risalah Islamic Boarding School toward Their Speaking Skill Development - Wildatul Fikra; Lafziatul Hilmi (Universitas Negeri Padang, 2023)
This research intended to know students’ perception on English camp program in MA female Ar-Risalah Islamic boarding school toward their speaking skill development. This program is implemented especially for grade tenth, that carried out for three days in first semester. This program already conducted for six years in the school, so the researcher believed it was important to to analyze how the students’ perception toward the activities. This study employed a qualitative methodology. The data were collected through questionnaire and interview. The questionnaire consisted 30 statements given to 110 students and interview consisted 3 questions given to 8 students. As a result of the study, most of the students gave positive responses toward English camp program in developing their speaking skill. Students found a place to thoroughly practice English at the English camp. It also had a great power to encourage students’ motivation to often practice speaking English with friends. They were more interested in practicing English in the English camp, because of many attractive and interesting learning activities